2018
DOI: 10.1016/j.redox.2017.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome b5 reductase is the component from neuronal synaptic plasma membrane vesicles that generates superoxide anion upon stimulation by cytochrome c

Abstract: In this work, we measured the effect of cytochrome c on the NADH-dependent superoxide anion production by synaptic plasma membrane vesicles from rat brain. In these membranes, the cytochrome c stimulated NADH-dependent superoxide anion production was inhibited by antibodies against cytochrome b5 reductase linking the production to this enzyme. Measurement of the superoxide anion radical generated by purified recombinant soluble and membrane cytochrome b5 reductase corroborates the production of the radical by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…Louis, MO, USA) were assessed by HPLC with fluorescence detection, as a quantitative measure of plasma superoxide anion levels, as described [37][38][39] . 2-EOH present in the samples was quantified by comparing with a calibration curve based on the reaction xanthine-xanthine oxidase from the method described by Michalski and cols 40 .…”
Section: Analysis Of Circulating 2-hydroxyethidium (2-eoh) Plasma Lementioning
confidence: 99%
“…Louis, MO, USA) were assessed by HPLC with fluorescence detection, as a quantitative measure of plasma superoxide anion levels, as described [37][38][39] . 2-EOH present in the samples was quantified by comparing with a calibration curve based on the reaction xanthine-xanthine oxidase from the method described by Michalski and cols 40 .…”
Section: Analysis Of Circulating 2-hydroxyethidium (2-eoh) Plasma Lementioning
confidence: 99%
“…Therefore, these results suggested a major contribution of lipid rafts to overall ROS/RNS production in our mature CGN cul- Previous works have shown that deregulation of several redox systems associated with neuronal lipid rafts can produce over shots of ROS and/or RNS, namely, superoxide anion by Cb5R3 [57,58], nitric oxide by nNOS [30,31,59,60], and hydrogen peroxide and superoxide anion by cytochromes P450 [61]. All these redox systems are flavoproteins, and DPI, a broad spectrum flavoprotein inhibitor, produced more than 90% inhibition of ROS/RNS production monitored by the dyes used in this work.…”
Section: The Production Of Ros That Is Inhibited By Mβcd Decreased During Cgn Maturation and This Is Reverted By Cb5r3silencingmentioning
confidence: 52%
“…This attenuation of ROS production in mature CGN can be reverted by silencing the expression of Cb5R3 to approximately 50%. Cb5R3 is a redox protein associated with lipid rafts, whose expression level increases approximately 2.5-fold from 5DIV to 9-10DIV [22], and whose deregulation leads to an overshot of superoxide anion production by CGN [16] and also of rat brain synaptic plasma membranes [14,57]. Therefore, our results show that Cb5R3 plays a major role in the attenuation of the overall ROS production in mature CGN, and reveal a major role of this protein as an antioxidant cellular defense against CGN exposure to extracellular neurotoxic oxidative insults.…”
Section: The Production Of Ros That Is Inhibited By Mβcd Decreased During Cgn Maturation and This Is Reverted By Cb5r3silencingmentioning
confidence: 99%
“…Over stimulation and clustering of CYB5R3 induced oxidative stress-mediated apoptosis of cerebellar granule neurons [ 386 ]. Independent of respiratory chain activities, the ascorbate-dependent NADH: cytochrome c oxidoreductase oxidation of NADH at CYB5R3 centers in lipid rafts is also a major source of extracellular superoxide [ 376 , 387 , 388 , 389 , 390 ] that can initiate lipid peroxidation. In Wistar rats, the deregulation of CYB5R3 promptly triggers apoptosis due to the overproduction of superoxide anions at neuronal plasma membranes [ 368 , 387 ].…”
Section: The Interdependence Between Membranes and Membraneless Organellesmentioning
confidence: 99%